Managing classrooms and student behavior : a response to intervention approach for educators - Frank, Catherine Lawless; Baldwin, Joni L.; Christman, Jennifer T.; Richards, Steve, 1954- (Routledge, 2019)
"Managing Classrooms and Student Behavior provides the essential information necessary for understanding and applying classroom and behavior management techniques with a Response to Intervention (RTI) approach. The presentation and application of information more closely resembles the actual decision-making approaches used by individuals and teams of teachers, schools, and districts. This introductory, reader-friendly textbook can be used in undergraduate or graduate level courses with special education or both special and general education candidates. A companion website provides key ancillary materials such as PowerPoint presentations, a test bank, and an instructor's manual"- Resumé vydavatel
Keywords: management třídy; lidské chování; class management; human behavior; elektronické knihy; učebnice; electronic books; textbooks